Europe’s Energy Shift: From Fossil Fuels to Renewable Energy - Jenei, Szonja; Módosné Szalai, Szilvia; Singh, Dhruv Pratap; Afadzinu, Kobla Sewornu; Poyda-Nosyk, Nina; Kálmán, Botond Géza; Dávid, Lóránt Dénes (Emerging Science Journal, 2025)
Objectives: This study explores the transformation of energy consumption in Europe between 2002 and 2022, focusing on the declining role of fossil fuels and the increasing significance of renewable and nuclear energy sources. The study also considers how countries with varying levels of economic development adopt different energy strategies and how these strategies correlate with shifts in energy usage. A circular economy approach that includes energy recovery from waste and resource reuse is a complementary aspect of sustainable energy transitions. Methods/Analysis: The per capita energy consumption data were analyzed through decile classification and cluster analysis to group countries with similar energy profiles. To explore the relationship between GDP and energy use—both total and renewable—linear and exponential regression models were applied. Outlier countries with atypical consumption trends were excluded to improve model reliability. Statistical analyses were conducted using SPSS, and Excel was used to support the visualization process. Findings: Six distinct clusters of energy consumption patterns emerged. In lower- and middle-GDP countries, renewable energy use showed a stronger exponential correlation with GDP growth than total energy use. While fossil fuel dependence has declined across most countries, the pathways taken have been diverse. High-GDP nations such as Iceland and Norway have demonstrated unique, resource-driven strategies. Novelty/Improvement: This study introduces a novel methodological blend of decile-based classification and clustering to enable clearer cross-country comparisons of energy use. The results also highlight the importance of excluding statistical outliers to improve regression precision. By integrating insights relevant to circular economy principles, the findings contribute to designing more effective and regionally adapted energy transition strategies.